2019
DOI: 10.1042/bsr20190476
|View full text |Cite
|
Sign up to set email alerts
|

Serum thrombospondin-2 is a candidate diagnosis biomarker for early non-small-cell lung cancer

Abstract: Thrombospondin-2 (THBS2) is a secreted protein overexpressed in numerous cancers and may function as a diagnostic tumor marker. The objective of the present study was to investigate the diagnostic performance of serum THBS2 in early stage non-small-cell lung cancer (NSCLC). Serum THBS2 and Cyfra21-1 level were evaluated in blood samples of 112 patients from NSCLC groups and 51 healthy control (HC) groups. Receiver operator characteristic (ROC) curves were used to evaluate the diagnostic significance. Serum THB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…TSP2 was proposed as prognosis marker in liver fibrosis, 47,48 non-alcoholic fatty liver disease, 49 and different cancers. [50][51][52][53] This study demonstrates that TSP2 is an important player in OA pathogenesis, with a positive correlation observed between TSP2 expression and synovial tissue inflammation, suggesting TSP2 could been developed as novel osteoarthritis marker. The pre-clinical experiments, which utilized TSP2 neutralizing antibody to ameliorate cartilage destruction in OA animal model, also showed the promising response.…”
Section: Discussionmentioning
confidence: 60%
“…TSP2 was proposed as prognosis marker in liver fibrosis, 47,48 non-alcoholic fatty liver disease, 49 and different cancers. [50][51][52][53] This study demonstrates that TSP2 is an important player in OA pathogenesis, with a positive correlation observed between TSP2 expression and synovial tissue inflammation, suggesting TSP2 could been developed as novel osteoarthritis marker. The pre-clinical experiments, which utilized TSP2 neutralizing antibody to ameliorate cartilage destruction in OA animal model, also showed the promising response.…”
Section: Discussionmentioning
confidence: 60%
“…A clinical study of patients with cancer in China has found signi cant heterogeneity in the distribution of serum THBS2 in various types of cancer compared with healthy control individuals [18]. Thrombospondin-2 might be a diagnostic marker of pancreatic, gastric, non-small-cell lung, and colorectal cancers [2,3,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Seeking effective biomarker is important to reduce incidence rate of NSCLC. Several genes including bromodomain PHD nger transcription factor (BPTF) [18], Serum thrombospondin-2 [19], CTAPIII/CXCL7 [20], c-MET [21], and so on. Accumulating evidence indicates that miRNAs can be biomarker of NSCLC.…”
Section: Discussionmentioning
confidence: 99%